Where have all the flowers gone? A call for federal leadership in deer management in the United States - Blossey, Bernd; Hare, Darragh; Waller, Donald M. (Frontiers in Conservation Science, 2024)
Forests in the United States continue to lose biodiversity and many fail to regenerate due to high deer (family Cervidae) abundance. Declines in biodiversity and overall ecosystem health due to high deer populations increases prevalence of wildlife and human diseases associated with increasing tick abundances and decreases forest resilience and the ability to deliver benefits provided by healthy ecosystems. In the eastern and midwestern United States, white-tailed deer (Odocoileus virginianus) are the main stressor, while in the western U.S. elk (Cervus elaphus) and black-tailed and mule deer (Odocoileus hemionus) can become equally problematic. Federal and State Wildlife Agencies are responsible for environmental stewardship and management of deer, migratory and endangered species, yet they lack authority to address human health concerns or commercial interests (we acknowledge tribal authority to manage wildlife as an important contributor to conservation). Furthermore, State Wildlife Agencies have retained their traditional focus to manage wildlife for recreational hunters while neglecting their obligations to manage wildlife in the interest of all citizens rather than special interest groups. Fragmented institutional arrangements and widely scattered responsibilities for human health, environmental conservation and management, agriculture, and commerce among tribal, federal, and state agencies have allowed deer impacts to grow into nationwide conservation and human health crises. Given that local, regional, and state-level initiatives have failed to provide appropriate remedies, federal leadership is now essential to integrate concerns among disciplines, policy domains, regions, habitats, and biota. We recommend developing a National Strategy to build strong collaborative efforts and diverse and inclusive relationships across environmental, human health and economic interests. These should reach beyond state boundaries to comprehensively address interrelated deer, human health, forest, and conservation crises. A well-coordinated and collaborative approach has the potential to overcome traditional turf battles between tribal, state, and federal interests by recognizing joint responsibilities and obligations to manage wildlife as a public trust resource. This collective approach can protect species before they become endangered, avoiding further declines in environmental and human health.